A detailed study of gravel bed flocculator performance - Trinh Thi Thanh; Vigneswaran, S.; Nguyen, Cong Thanh; Samorn Muttamara; Chongrak Polprasert; German Academic Exchange (DAAD) Federal Republic of Germamy (Bangkok : Asian Institute of Technology, 1985)
Flocculators are used in water and waste water treatment process to remove turbidity, colour, taste, odour, etc. The gravel bed flocculator performance was studied for various operating parameters such as gravel size, gravel bed height, the approach velocity and for different concentration of Kaolin clay. The performance was studied in terms of turbidity removal efficiency, floc growth and headless development. The removal efficiency for the three gravel sized used ranged 62-94% and the suitable bed depth was found 65.cm. The velocity gradient in the bed increased as flocculation run proceeds due to headless development and it ranged between 18-75 s. The non dimensional parameter, Gt for successful flocculation and suspended solid removal varied from 2 x 10 3 to 2.7 x 10 4 which is lower compared to that in conventional flocculation (10 4 - 10 5 ). Empirical relationships between G, V and T can be formulated from limited number of experiments with the raw water to be treated, which will then be useful in the selection of design parameters. In the present study, such an empirical relationship was formulated for Kaolin clay suspension in the presence of alum. G=0.935 v 0389 t0.24 The gravel bed flocculator can be used with advantage for small communities and villages because it not only achieves uniform intensity of agitation throughout the gravel bed but also does not require any power, mechanical equipment and skilled labour.
A thesis submitted in partial fulfillment of the requirements for the degree of Master of Science, School of Environment, Resources and Development
Thesis (M.Sc.) - Asian Institute of Technology, 1985
Keywords: Flocculation